QSM is an imaging biomarker for chronic glial activation in multiple sclerosis lesions. Issue 4 (11th March 2021) - Gillen, Kelly M.; Mubarak, Mayyan; Park, Calvin; Ponath, Gerald; Zhang, Shun; Dimov, Alexey; Levine‐Ritterman, Maya; Toro, Steven; Huang, Weiyuan; Amici, Stephanie; Kaunzner, Ulrike W.; Gauthier, Susan A.; et al.
Abstract: Background: Inflammation in chronic active lesions occurs behind a closed blood–brain barrier and cannot be detected with MRI. Activated microglia are highly enriched for iron and can be visualized with quantitative susceptibility mapping (QSM), an MRI technique used to delineate iron. Objective: To characterize the histopathological correlates of different QSM hyperintensity patterns in MS lesions. Methods: MS brain slabs were imaged with MRI and QSM, and processed for histology. Immunolabeled cells were quantified in the lesion rim, center, and adjacent normal‐appearing white matter (NAWM). Iron + myeloid cell densities at the rims were correlated with susceptibilities. Human‐induced pluripotent stem cell (iPSC)‐derived microglia were used to determine the effect of iron on the production of reactive oxygen species (ROS) and pro‐inflammatory cytokines. Results: QSM hyperintensity at the lesion perimeter correlated with activated iron + myeloid cells in the rim and NAWM. Lesions with high punctate or homogenous QSM signal contained no or minimally activated iron − myeloid cells. In vitro, iron accumulation was highest in M1‐polarized human iPSC‐derived microglia, but it did not enhance ROS or cytokine production. Conclusion: A high QSM signal outlining the lesion rim but not punctate signal in the center is a biomarker for chronic inflammation in white matter lesions.